2016
DOI: 10.1080/03601234.2016.1241640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nozzle types and 2,4-D formulations on spray deposition

Abstract: The objective of this study was to evaluate the effects of nozzle types and 2,4-D formulations on spray deposition on different targets. Two field experiments were carried out in a completely randomized design, and treatments were arranged in a factorial scheme. Species in experiment 1 were Sumatran fleabane (Conyza sumatrensis) and Brazil pusley (Richardia brasiliensis) and in experiment 2 were soybeans (Glycine max) and Benghal dayflower (Commelina benghalensis). For both experiments, the first factor corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
0
12
1
7
Order By: Relevance
“…For example, the application of several chemicals through the AIXR nozzles increased the VMD in all situations compared to the standard XR nozzle (Ferguson et al 2015; Martini et al 2015). In another study, both 2,4-D choline and DMA formulations showed lower drift potential when applied through the ADIA nozzle (flat fan with air induction) in relation to the XR nozzle (Contiero et al 2016). Thus, GF-3073 and the air induction nozzles are a powerful combination for reducing 2,4-D movement to nontarget crops in the areas where 2,4-D-resistant crops are grown.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the application of several chemicals through the AIXR nozzles increased the VMD in all situations compared to the standard XR nozzle (Ferguson et al 2015; Martini et al 2015). In another study, both 2,4-D choline and DMA formulations showed lower drift potential when applied through the ADIA nozzle (flat fan with air induction) in relation to the XR nozzle (Contiero et al 2016). Thus, GF-3073 and the air induction nozzles are a powerful combination for reducing 2,4-D movement to nontarget crops in the areas where 2,4-D-resistant crops are grown.…”
Section: Resultsmentioning
confidence: 98%
“…Although both chemical and mechanical tools have shown individual effects to control spray drift under field conditions, specific associations among them can result in different interactions. For example, a 2,4-D dimethylamine (DMA) formulation applied through drift-reduction nozzles had higher spray drift potential than did a 2,4-D choline formulation (Contiero et al 2016).…”
mentioning
confidence: 99%
“…Recent advances with pesticide application technology includes spray nozzles (i.e., spray tips) that improve delivery of foliar applied herbicides (Contiero et al, 2016;Creech et al, 2015), and also utilize correct spray nozzles and techniques to reduce spray drift to non-target sites (Grella et al, 2020;Kalsing et al, 2018). The spray nozzle produces a spray pattern which contains spray droplets in various sizes depending on the nozzle type (ASABE, 2009;Lake, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the adoption of these products in seed treatment, when compared to foliar application, reduces the number of operations to be carried out after the emergence of the crop. As a consequence, there is a reduction in the plant kneading in the crop and in soil compaction (Ferreira et al, 2020), a reduction in the risk of losses due to spraying (Contiero et al, 2016), beside saving machine, labor and time to spray the crop.…”
Section: Introductionmentioning
confidence: 99%